Peran Pendidikan sebagai Modal Manusia dalam Mendorong Pertumbuhan Ekonomi yang Berkelanjutan - Yuliyanto, Riyan (Journal of Social Science Education, 2024)
The importance of education to promote sustainable economic growth has been objectively demonstrated in this study, and human capital has long been considered the most characteristic aspect of economic systems. This study intends to empirically investigate the role of education as human capital in relation to sustainable economic growth from various previous research results. A qualitative research approach with a literature study is used to get an overview of the correlative-synergistic dimension. As a result, Indonesia as a developing country must devote significant resources to building a strong education system in line with one of Indonesia’s golden visions of 2045 to achieve sustainable economic development centered on knowledge and high quality human resources.Keywords: Education, Human Capital, Sustainable Economic Growth.Doi: https://doi.org/10.23960/JIPS/v5i1.19-25